2009
DOI: 10.1177/0957926508097097
|View full text |Cite
|
Sign up to set email alerts
|

Political grandstanding and the use of proverbs in African political discourse

Abstract: In Africa, the transmission of the overwhelming complexity of the people's day-to-day experiences are deeply rooted in the continent's rich cultural artistry. Proverbs are the most widely and commonly used in the continent's long standing history of oral arts. Proverbs are regarded as repositories of the people's collective social, political and cultural wisdom and as analytic tools of thought. This paper analyses how different Kenyan politicians and political parties used proverbs to strengthen and further th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The findings are in agreement with some African studies on language acquisition like the studies by Orwenjo (2009) and Makeni (2007). Makeni (2007), for example, reports that the age of the child affects the acquisition of concordial morphemes among the children acquiring Lukhayo as their L1.…”
Section: Age and Lexical Inventionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings are in agreement with some African studies on language acquisition like the studies by Orwenjo (2009) and Makeni (2007). Makeni (2007), for example, reports that the age of the child affects the acquisition of concordial morphemes among the children acquiring Lukhayo as their L1.…”
Section: Age and Lexical Inventionsupporting
confidence: 93%
“…In a related study conducted by Orwenjo (2009), it was found out that children resort to lexical innovations as a "stop-gap" measure to cope with lexical gaps that are hindrances to smooth communication. The current study adopts the same interpretation for cases of lexical importation among the children.…”
Section: Age and Lexical Importationmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue tackles the emergence of what I would loosely term, the Englishes of politics around the globe. There has been some valuable and interesting work in the area of culturally specific political discourse, including political slogans in China (Lu, 1999), proverbs in African political discourse (Orwenjo, 2009), inclusiveness in political campaigning in Trinidad and Tobago (Esposito, 2017), and delegitimization in the Arab Spring (Bhatia, 2015), to mention a few. However, there is scope for further work in the area of how culture‐specific politics shapes language, and how, in turn, language shapes local politics.…”
Section: National Identity Legitimacy and World Englishesmentioning
confidence: 99%
“…That denominations for food are often the target of such political thrusts is not accidental since the origin or supposed origin of food is often transparent through the terms used, such as in the cases above, through compounds with a premodifying adjective denoting the country of origin or through borrowing the word used from the language of the country of origin (for food and politics, cf. also Orwenjo 2009 for the use of proverbs, also on food, in political campaigns in Africa).…”
Section: Morphology and Word Formationmentioning
confidence: 99%